2008
DOI: 10.3748/wjg.14.6578
|View full text |Cite
|
Sign up to set email alerts
|

Colonic perforation in Behçet’s syndrome

Abstract: A 17-year-old gentleman was admitted to our hospital for headache, the differential diagnosis of which included Behçet's syndrome (BS). He developed an acute abdomen and was found to have air under the diaphragm on erect chest X-ray. Subsequent laparotomy revealed multiple perforations throughout the colon. This report describes an unusual complication of Behcets syndrome occurring at the time of presentation and a review of the current literature of reported cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
7
0
6
Order By: Relevance
“…Bu hastalarda ileoçekal bölge tutulumu yaklaşık %75'dir (6). Vakaların %1'inden daha azında ülseratif değişiklikler görülür (17). İntestinal ülserler, aftöz ya da derin ve zımba deliğine benzer ("punched-out") yuvarlak ve oval görünümdedir (7,15).…”
Section: Kolonik Behçet Hastalığında Histomorfolojiunclassified
See 2 more Smart Citations
“…Bu hastalarda ileoçekal bölge tutulumu yaklaşık %75'dir (6). Vakaların %1'inden daha azında ülseratif değişiklikler görülür (17). İntestinal ülserler, aftöz ya da derin ve zımba deliğine benzer ("punched-out") yuvarlak ve oval görünümdedir (7,15).…”
Section: Kolonik Behçet Hastalığında Histomorfolojiunclassified
“…Ülserasyonlar lokalize ve diffüz biçimde iki tipte oluşabilir (6). Ülserler penetrasyon, perforasyon ve kanamaya sebep olabilir (14,17). Ülserli hastaların %50'inde perforasyon ve penetrasyon oluşur (14).…”
Section: Kolonik Behçet Hastalığında Histomorfolojiunclassified
See 1 more Smart Citation
“…Ozbiljne manifestacije bolesti razvijaju se kod oko 25% bolesnika i to ireverzibilni vaskulitis krvnih sudova retine kod 15%, tromboembolijske komplikacije na velikim krvnim sudovima kod 8,5%, zahvatanje centralnog nervnog sistema kod 3,2-8%, gastrointenstinalne manifestacije kod 2,8-7,6%, perforacija creva kod 1% i letalan ishod bolesti kod 2% bolesnika [4][5][6][7][8] . Većina opisanih slučajeva sa gastrointestinalnim manifestacijama je iz zemalja istočnog Mediterana i iz Japana gde je i prevalencija Behčetove bolesti najveća 3,4 .…”
Section: Diskusijaunclassified
“…Deep ulcers in the GI tract that are seen in BD are the major causes of severe complications, such as severe bleeding and perforation. There are only a few studies that have reported colonic perforations due to BD (2,3). In this article, we report a patient with BD who underwent an emergent operation because of acute abdomen, developing secondary to multiple perforations of the ascending colon and terminal ileum.…”
mentioning
confidence: 99%